COMPETITION AND COMPETITIVENESS OF SECTOR OF COMMERCIAL BANK (Research Bulletins of the Faculty of Economic Sciences, 2021)
Operations taken have contributed to their growth of competitiveness by polish commercial banks. Changes in largeness of asset and doubts do not leave capitals, that process of conversion is concentrated on scaling up of polish competitiveness of bank. Competitiveness of activity of bank gauged traditional measure net interest margin it has exerted upward trend distinctly. It does not exhaust the present abstract theme, but there is input to above-mentioned question only. Introduced accounts present base for farthest consideration and in this range analyses.